2017
DOI: 10.5194/gmd-10-385-2017
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of street trees within the solar radiative exchange parameterization of TEB in SURFEX v8.0

Abstract: Abstract. The Town Energy Balance (TEB) model has been refined and improved in order to explicitly represent street trees and their impacts on radiative transfer: a new vegetated stratum on the vertical plane, which can shade the road, the walls, and the low vegetation has been added. This modification led to more complex radiative calculations, but has been done with a concern to preserve a certain level of simplicity and to limit the number of new input parameters for TEB to the cover fraction of trees, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 57 publications
(73 reference statements)
1
52
0
1
Order By: Relevance
“…The modification of solar radiation by the buildings calculated by TEB has been evaluated by Redon et al . () using the building resolving model SOLENE as a reference. Their results show that TEB accurately simulates the radiation captured by the wall and the ground.…”
Section: Mesoscale Atmospheric Model Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification of solar radiation by the buildings calculated by TEB has been evaluated by Redon et al . () using the building resolving model SOLENE as a reference. Their results show that TEB accurately simulates the radiation captured by the wall and the ground.…”
Section: Mesoscale Atmospheric Model Simulationsmentioning
confidence: 99%
“…The explicit treatment of high vegetation implemented by Redon et al . () will circumvent this restriction in future versions of TEB. Similarly, for rural areas, the ISBA vegetation model employed here also only considers the vegetation at the surface.…”
Section: Mesoscale Atmospheric Model Simulationsmentioning
confidence: 99%
“…ground vegetation, street trees, vegetated walls and green roofs). This required development of the TEB model (Masson, 2000) to consider, and further evaluate, such scenarios (Lemonsu et al, 2012;De Munck et al, 2013;De Munck et al, 2018;Redon et al, 2017). Using a complete vegetation and soil model to represent green roofs, De Munck et al (2018) showed that green roofs would not have a significant effect on air temperature at street level, contrary to ground vegetation and trees.…”
Section: Main Challenges Scientific Novelty and Innovation Of Solutimentioning
confidence: 99%
“…κ watr is a complex function accounting for thermal stratification of water and surface friction velocity. To reduce complexity, and assuming a mixed homogeneous water layer, a constant κ watr is selected based on shallow lakes reported in Salas De León et al (2016). The change in temperature T ( • C) is the difference between the water temperature T surf,watr ( • C) and the soil temperature beneath the water layer T soil ( • C).…”
Section: Simple Water Body Modelmentioning
confidence: 99%
“…The Town Energy Balance (TEB) model (Masson, 2000) has emerged as a popular urban area parameterization scheme. The TEB-Veg (Lemonsu et al, 2012;Redon et al, 2017) variation includes urban vegetation and provides functionality to assess cooling impacts of GBI. However, the TEB-Veg model configuration and application requires a level of modelling skill normally outside the capability of environmental consultants.…”
mentioning
confidence: 99%